Transformation of the Countries of Central and Eastern Europe – an Attempt at Comparing Croatia and Slovenia - Lubik-Reczek, Natasza (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2015)
For over a dozen years changes have been taking place in Central and Eastern Europe which are explained in the categories of systemic transformation. “Systemic transformation” is the term most widely used to describe the social change that began in that part of Europe after 1989. A term close, albeit narrower, in meaning is the “political transformation” which describes the phase of radical change of social order in the formal and legal aspect. Analysing the transformation of Central and East European countries one should not disregard the Balkan states. Those states have new constitutions, laws concerning political parties and new electoral statutes. They have opened the road to a competitive party system and the political system based on democratic principles.

W Europie Środkowej i Wschodniej od kilkunastu lat zachodzą zmiany, które wyjaśniane są w kategoriach transformacji systemowej czy ustrojowej. Transformacja systemowa jest najczęściej używanym pojęciem do opisu zmiany społecznej, która rozpoczęła się w tym rejonie Europy po 1989 r. Zbliżonym pojęciem, choć węższym jest transformacja ustrojowa, która opisuje fazę radykalnej zmiany ładu społecznego w aspekcie formalno-prawnym. Analizując transformację państw Europy Środkowej i Wschodniej, zwrócić należy również uwagę na państwa bałkańskie. Zostały w nich uchwalone nowe konstytucje, ustawy o partiach politycznych i ordynacje wyborcze. Otworzyły one drogę do konkurencyjnego systemu partyjnego oraz systemu politycznego opartego na zasadach demokracji.
Transformacja w państwach Europy Środkowej i Wschodniej – próba porównania Chorwacji i Słowenii
Keywords: transformation; Central and Eastern Europe; Croatia; Slovenia; transformacja; Europa Środkowa i Wschodnia; Chorwacja; Słowenia